Türk Halk Oyunlarında Kullanılan Araç Ve Aksesuarlarının Anlam Ve İşlevleri Üzerine İncelemeler - Gicili, Suna (Sosyal Bilimler Enstitüsü, 1999)
Bu çalışmada önce tarihsel süreç içerisinde dansın gelişiminden bahsedilmiş ve bu süreç ile birlikte ne türden gelişme ve değişmeler olduğu aktarılmaya çalışılmıştır. Dansın (oyunun) ilkel insanla birlikte başladığı ve danslar sırasında kullanılan araç ve aksesuarların biçimsel ve işlevsel açıdan göstermiş oldukları gelişmeleri takip etmekte yardımcı olacağı inancıdayız. Halt Oyunları (Dansları) gösterimleri sırasında kullanılan araç ve aksesuarların yüklendikleri anlam ve işlevleri hakkında bilgiler verildikten sonra her iki unsuru da doğrudan ve dolaylı olarak etkileyen ya da destekleyen unsurlar ile ilgili bilgiler verilmiş, kostüm-aksesuar, oyun-araç birliktelikleri ve Halk Oyunlarının sergilendiği mekanlar ile aralarındaki ilişkiler hakkında bilgiler verilmeye çalışılmıştır. Yine bu araç ve aksesuarlara ilişkin tespit edilen isim listeleri verilmiş. Türk Halk Oyunlarında yaygın olarak kullanılmasının bir sebebi olarak el sanatlarının (dokumacılık, oymacılık, maden işlemeciliği vb.) Anadolu kültüründe yaygın ve yerleşik olmasının önemi bir kez daha ortaya çıkmıştır.

The combination of dance and melodie which have been developing one within the other through human history and are performed in the present, is perceived as the most effective and passionate one of fine arts. With this feature, it is seen as the most intensive area for research, improvement and staging studies. Therefore, this study has been begun to bring up the aesthetic values, meanings and fuuction of instruments and accessories which are used in an area where feelings and thoughts are successfully shared among the societies and expressed in an universal point of view. However, the studied subject has a frame in which just the instruments and accessories used in dances of Turkish Folklore are observed and it is localized around the Turkish culture. In the begining of the study, it is observed that there are information and material about the subject in various sources although they are limited and disorganized. Therefore, on the first hand, informantion in these sources are gathered together and they are evaluated in a sense of thesis. Used material is obtained by searching written material such as encyclopedia, books, magazines etc., making used of various private and official archives, interviewing some people having local knowledge and some experts, getting pictures from private and official collections, using the ix academic and individual knowledge composed of experiences in the area of Turkish Folk Dances since 15 years. However, it should be explained that field research could not be done sufficiently due to the lack of time, economic limitations and because of the great dimensions and deepness of the selected subject. The studied subject is examined and evaluated in three main directions according to studying plan and thesis composition. The first one covers the fundamental and preliminary information with a general introduction to definition and examplanation of some concepts about dance, the history of costume and accessories according to their etymological, visual and functional features. Next, the instrument, and accessories used in Turkish Folk Dance are classified according to their structural and physical characteristics. As a result of this classification, the relation between the structural and physical characteristics of instruments and accessories and their meanings and functions in dance is explained in details with the related pictures. And the last, in adifferent direction, the instruments and accessories used in Turkish Folk Dances are observed according to male dances, female dances and common dances. The subject is more limited to dances and supported by various informantion and related photographs. As before indicated, "Studies About Meanings And Functions Of instruments And Accessories Used in Turkish Folk Dances" which is a very wide subject and needs field studies, covers many subtitles, each of them is a subject of different theses. There fore, if this subject is examined and searched in an academic view of point, scientifically, it will be more clear and fiil a lack in Turkish culture. This study will also be a base for next coming studies
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1999
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 1999
Keywords: Halk Bilimi (Folklor); Aksesuar; Folklor; Halk oyunları; Oyunlar; Türk halk oyunları; Folklore; Accessory; Folklore; Folk dances; Games; Turkish folk dances